PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN DI BEI - Y. Yudha Dharma Putra; Ni Luh Putu Wiagustini (Universitas Lambung Mangkurat, 2013)
High corporate value of a company will attract investors to invest in the company. Company value on companies that went public in the long-term improvement is affected by profitability, the higher the value of the company’s profitability is also higher the value of the company, and the lower the profitability of a company reflects the low value of the company. Investors buy stocks in companies that go pubilc in order to benefit from the investments made. This study aimed to analyze the influence of Liquidity and Leverage on Profitability and Value.The population used in this study is a banking company listed in Indonesia Stock Exchange (BEI) in 2007 to 2011 by 31 companies. The sampling technique used was purposive sampling. Samples taken in this study were 20 companies for 5 years. Techniques of data analysis in this study using Path analysis.The results showed that: 1) no significant positive effect of liquidity on profitability. 2) leverage gives a significant positive effect on profitability. 3) liquidity is not significant positive effect on a firm value. 4) Liquidity positive effect on company value through profitability. 5) Leverage gives a significant positive effect on firm value. 6) Leverage has a positive effect on firm value through profitability. 7) Profitability gives a significant positive effect on company value.